Axillary metastatic adenopathy due to hidden breast primary cancer - Ernesto Arias Beatón; Nancy Nuri Múnder Despaigne; Martha Beatriz Arias Beatón (Centro Provincial de Información de Ciencias Médicas, 2019)
The clinical report of a 56 year-old patient who went to the Oncology Service of the Government Hospital from Mbabane, in Swaziland, for suffering an adenopathy in the left armpit with a clinical course of several months, confirmed by echography is described. An aspiration biopsy with fine needle was carried out whose result revealed the metastasis of a ductal carcinoma. The preoperative studies were completed, the stage of the clinical entity was determined (IIA) and the patient was referred to the Surgery service to carry out an axillary dissection and then to apply radiotherapy in the armpit and breast.